Drug Induced-Stevens Johnson Syndrome: A Case Report - George, Neethu; Johnson, Persis; Thomas, Jisna; Mariya, Aloshin (Journal of Pharmacy Practice and Community Medicine)
Background: Stevens–Johnson syndrome (SJS) is one of the severe forms of cutaneous adverse drug reactions (CADRs). Stevens-Johnson syndrome (SJS) and toxic epidermal necrolysis (TEN) are severe idiosyncratic reactions.They are most commonly caused by medications, which are characterized by fever and mucocutaneous lesions leading to necrosis and sloughing of the epidermis. Stevens Johnson Syndrome (SJS) and TENS (Toxic Epidermal Necrolysis Syndrome) another form of SJS-are severe adverse reactions to medication. Methods: This is an observational type of case report which we observed in our hospital on regular ward rounds. Results: This is a case report of Paracetamol induced SJS. Causality assessment of this event with Naranjo’ scale suggests “Probable”. Conclusion: This case concludes that severe hypersensitivity reactions like SJS can caused by acetaminophen use and which can be potentially life threatening which needs the additional treatment.
Keywords: Stevens Johnson Syndrome; Toxic Epidermal Necrolysis Syndrome; Adverse drug reactions